EFFECT OF WELL BORE MIXING VOLUME ON NON-AXISYMMETRICAL TRANSPORT IN A CONVERGENT RADIAL TRACER TEST - Chen J.S.; Liu C.W.; Chen C.S.; Liao C.M. (My University, 2003)
When tracers are introduced into an injection borehole, the resulting non-axisymmetrical plume undergoes transverse dispersion during transport to the extraction well in a radially convergent tracer test. The transverse dispersivity governs the shape of the breakthrough curves observed at a point between the extraction and injection wells. Accordingly, concentrations monitored at the extraction and observation wells can be used to simultaneously determine the longitudinal and transverse dispersivities. This study presents a two-dimensional Laplace transform finite-difference (LTFD) model to examine the effect of the finite mixing volume of an injection well bore on non-axisymmetrical transport during a radially convergent tracer test. The developed model was compared to the analytical solution to evaluate the accuracy of the model. Comparative results suggest that the LTFD model with an upstream weighting technique incorporating an extra fine mesh, can be used to effectively and accurately solve the radial advection-dispersion equation with large Peclet numbers. Two tracer tests with distances 5 and 25 m, were considered to investigate the effect of inter-well distance on the role of injection well bore storage. Simulation results reveal that injection well bore mixing volume significantly decreases the peak concentration and spreads out the breakthrough curve obtained in the tracer test with a 5 m inter-well distance. When the inter-well distance increases to 25 m, the injection well bore mixing volume weakly affects the tracer transport.
Keywords: TRANSVERSE DISPERSION; WELL BORE MIXING VOLUME; LAPLACE TRANSFORM FINITE-DIFFERENCE METHOD; NON-AXISYMMETRICAL TRANSPORT